Association between maternal height and mode of delivery in nulliparous Japanese women. Issue 12 (1st October 2020) - Kuritani, Yoshihiro; Hayashi, Shusaku; Yamamoto, Ryo; Mitsuda, Nobuaki; Ishii, Keisuke
Abstract: Aim: The primary aim of this study was to examine the association between maternal height and mode of delivery in nulliparous Japanese women. The secondary aim was to examine the association between maternal height and maternal and neonatal morbidities. Methods: This retrospective cohort study included women who gave birth at Osaka Women's and Children's Hospital, a tertiary perinatal center in Japan, from January 2015 to December 2017. Nulliparous Japanese women with singleton gestation, who went into labor at term were included in the study. The primary outcome was mode of delivery, and the secondary outcomes were maternal and neonatal morbidities. The relationships between maternal height and the outcomes were evaluated using multivariate logistic regression analysis adjusted for potential confounders. Maternal height was categorized into five groups with 5‐cm increments for the analysis. Results: A total of 1593 women were analyzed in this study. Shorter women had higher rate of cesarean delivery (CD) than taller women. There were no significant differences in the rates of operative vaginal delivery, maternal morbidity and neonatal morbidity among the maternal‐height groups. The adjusted odds ratios (95% confidential interval) of maternal heights of <150 cm, 150–154 cm, 160–164 cm and ≥165 cm for CD, compared with a maternal height of 155–159 cm, were 3.56 (1.79–7.09), 1.68 (1.06–2.64), 0.63 (0.40–1.00) and 0.57 (0.30–1.01), respectively. Conclusion: Shorter nulliparous Japanese women were more likely to undergo intrapartum CD. However, the rates of maternal and neonatal morbidities in shorter women were similar to those in taller women.